2014
DOI: 10.1080/03004430.2014.963066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and stability of active play, restricted movement and television viewing in infants

Abstract: This study describes engagement in and stability of physical activity and sedentary behaviours in early life, and assesses associations with sex, maternal education and developmental stage. Maternal-report data at child age 4, 9 and 20 months were collected from 542 families in the Melbourne Infant Feeding Activity and Nutrition Trial Program. Parents estimated average time per day their child spent in active pursuits or pursuits that restricted movement. With increasing age, children generally spent more time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…Similar results were observed when the level of moderate to vigorous physical activity was assessed [130]. Very little evidence is available for younger children although recently, Hesketh et al have found an association between maternal education and infant time spent outdoors and time spent free to move around (proxies for physical activity) [131].…”
Section: Lack Of Physical Activitysupporting
confidence: 64%
“…Similar results were observed when the level of moderate to vigorous physical activity was assessed [130]. Very little evidence is available for younger children although recently, Hesketh et al have found an association between maternal education and infant time spent outdoors and time spent free to move around (proxies for physical activity) [131].…”
Section: Lack Of Physical Activitysupporting
confidence: 64%
“…Increasing time spent on the ground over the first year of life (from 24% at 3 months to 48% at 12 months) suggests that caregivers provide more opportunities for older infants to practice developing motor skills and thus to independently choose how to transition between positions. Both the current study and past work suggest that time spent reclined in infant furniture and held off the ground gives way to allow older infants more time in unrestricted activity (Hesketh, Crawford, Abbott, Campbell, & Salmon, ). This shift likely depends on caregivers recognizing improvements in infants’ motor abilities, caregiver beliefs about promoting motor abilities (Keller, Yovsi, & Voelker, ), beliefs about safety (Hnatiuk et al., ), as well as nonmotor changes in infant development (e.g., the ability to self‐soothe may allow infants to be held less often).…”
Section: Discussionsupporting
confidence: 51%
“…A wide variety of experiences can be studied if they can be distilled into 3–4 short questions with a coding scheme that is easy for caregivers to follow. For example, sedentary time (e.g., TV watching, passive play) versus active time (unrestricted movement) in infancy relates to health and developmental outcomes, but studies have relied on crude caregiver report measures or more expensive, technically demanding accelerometer measurements (Downing, Hnatiuk, & Hesketh, ; Hesketh et al., ; Hnatiuk et al., ). Opportunities for learning about objects (Ross‐Sheehy et al., ; Soska et al., ) could be measured by categorizing the how often infants manipulate objects and the types of objects encountered.…”
Section: Discussionmentioning
confidence: 99%
“…For infants less than 6 months old, caregivers should provide daily “tummy time” (time awake in the prone position) and opportunities for infants to move freely by engaging them unrestrained on the floor (in prone or supine position) and limit the use of equipment that restricts movement, such as bouncy seats or swings. Despite these recommendations, few studies have described patterns of infant tummy time, unrestrained floor time, and movement‐restricting time .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that health literacy, education, and ethnicity are related to infant activity. Hispanic mothers and those with inadequate health literacy reported less tummy time , and university‐educated mothers provided more play time than those with less education . There has been limited study of movement‐restricted time .…”
Section: Introductionmentioning
confidence: 99%